Cracks before the crisis: Polarization prior to COVID‐19 predicts increased collective angst and economic pessimism. (26th June 2022) - Crimston, Charlie R.; Selvanathan, Hema Preya; Álvarez, Belén; Jetten, Jolanda; Bentley, Sarah; Casara, Bruno Gabriel Salvador; Ionescu, Octavia; Krug, Henning; Steffens, Niklas K.; Tanjitpiyanond, Porntida; Wibisono, Susilo
Abstract: We examine how polarization within societies is associated with reduced confidence in national responses to the coronavirus disease 2019 (COVID‐19) crisis. We surveyed 4, 731 participants across nine countries at Wave 1 (France, Germany, Indonesia, Italy, Netherlands, Spain, Thailand, the United Kingdom and the United States), and then, at Wave 2 (3 months later), we recontacted 840 participants from two countries (the United Kingdom and the United States). We found that perceived polarization in the years preceding COVID‐19 predicted an enhanced perception that a country's COVID response was anomic (i.e., disorganized, chaotic), which in turn predicted greater collective angst and economic pessimism. Moreover, polarization measured at Wave 1 continued to predict perceptions that the COVID‐19 response was anomic at Wave 2, and, in turn, enhanced collective angst, pessimism, and the perception that dramatic political change was required to recover from COVID‐19. Our findings highlight how polarization may be associated with reduced confidence in leaders and governments at times of crisis, and how this predicts future‐focused anxiety and pessimism.